PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SDN PABELAN 2 KARTASURA - Saifur Robbi, Royan; Sudarmilah, Endah (Infotronik : Jurnal Teknologi Informasi dan Elektronika, 2024)
The school library at SD Negeri Pabelan 2 Kartasura contains various kinds of book collections, such as books supporting teaching and learning activities or textbooks, encyclopedias, language dictionaries, and storybooks. The results of observations and interviews conducted by the author with one of the teachers of SDN Pabelan 2 Kartasura, found that the system running in the library of SDN Pabelan 2 Kartasura has not run optimally because it is still done manually, such as book loan transactions are still carried out by writing data related to borrowing into a transaction book which often causes problems in its management so that loss often occurs. This research aims to design a web-based library information system that is expected to be used for the library system at SDN Pabelan 2 Kartasura. The system development method used to design the library information system at SDN Pabelan 2 Kartasura is scrum. According to the points that have been interpreted the system built has a sufficient level of reliability with the score obtained is the average score, which is 68. The web-based library information system at SDN Pabelan 2 Kartasura was successfully developed and runs well.